VALUASI EKONOMI KEKAYAAN SUMBERDAYA KELAUTAN JAWA BARAT SELATAN - Iwang Gumilar; Agus Ruswandi (CR JOURNAL (CREATIVE RESEARCH FOR WEST JAVA DEVELOPMENT), 2015)
The research aims to conduct an economic valuation of the wealth of marine resources in the South Coastregion West Java with a technique to quantify the value of resources in monetary terms. The experiment wasconducted September-December 2012 include Ciamis, Tasikmalaya, Garut, Cianjur, Sukabumi. Datacollected include secondary data and primary data. Secondary data was collected from relevant agencies,primary data collected through field observation and Focus Group Discussion. Analysis methode was usedescription analysi. Economic valuation used Total Economic Valuation (TEV) approachs, involved renewableresources such as mangrove resources, fisheries culture (fond and marine culture), and fishing; nonrenewableresources (mining); and environmental services (tourism activities). The results of this research obtained theeconomic value (present value with a discount factor of 16%) in the marine resources of the South West Javain 2012 for renewable resources amounted to Rp 1.408.989.172.400, which consists of the present value ofthe economic value of fish resources Rp. 1,345,910,309,000; aquaculture Rp. 60,725,829; coral reefresources. Rp 9,138,987,443; seagrass resources Rp. 46,367,631,672; and mangrove resource Rp.7,511,518,456. The total economic value of nonrenewable resources (iron/Fe deposit) was USD 31,950trillion; and the economic value of tourism services was Rp. 3,558,263,040,000.